Commercial Potential of Pelagic Sargassum spp. in Mexico - López Miranda, José Luis; Celis, Lourdes B.; Estévez, Miriam; Chávez, Valeria; van Tussenbroek, Brigitta I.; Uribe-Martínez, Abigail; Cuevas, Eduardo; Rosillo Pantoja, Izarelly; Masia, Luis; Cauich-Kantun, Citlali; Silva, Rodolfo (Frontiers in Marine Science, 2021)
The recent periodic influx of massive quantities of pelagic Sargassum spp. (sargasso) into the Caribbean has posed ecological, social, and economic challenges to the region. Sustainable use of the biomass is crucial to mitigate negative impacts of beached algae. The current uses of sargasso in Mexico are reviewed, and a biorefinery approach is proposed to optimize its commercialization. The commercialization potential of sargasso in the Mexican Caribbean is analyzed using the strengths, weaknesses, opportunities, and threats (SWOT) analysis. The unpredictability of the influx to the Mexican shores is considerable, both in time and space, also, some areas receive consistently more sargasso than others. The lack of available technology, local infrastructure and regulations concerning sargasso are relevant, as is the urgent need to establish proper regulatory measures. In the context of the Mexican legal system, the category “special waste” can best be applied to sargasso that is collected from the beach or nearshore waters for the purpose of regulation. Lessons learnt from in Mexico may be applied elsewhere, with adaptations for each specific location. More importantly, mutual understanding of the constraints and possibilities of sargasso management in other countries, or territories, may facilitate the coordinated management of this transboundary macroalgae bloom.